2023
DOI: 10.3390/su15108394
|View full text |Cite
|
Sign up to set email alerts
|

Cellulolytic Bacillus Strain: Production Optimization Using Wheat Bran under Solid-State Fermentation and Investigation of Its Probiotic Potential

Taroub Bouzaiene,
Manel Ziadi,
Malek Enneifer
et al.

Abstract: Attention to the association of cellulolytic bacteria with probiotic potential as an additive in animal feeding has risen in the last decades. Such additive use in livestock feed is essential in improving animal health, growth, and production performances. This study was designed to identify probiotic characteristics and test the cellulolytic ability of Bacillus strains isolated from the dromedary gastrointestinal tract. Thus, thirty-two Bacillus strains were tested for their cellulolytic ability on cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A variety of commercial probiotics for swine are currently available in the market, and small doses of these additives are frequently used. One study revealed that probiotics typically accounted for USD 13.65 billion in 2019 and are estimated to increase by 6.1% in 2027, depending on the manufacturer and the product’s active components [ 151 ]. In commercial pig farming, higher growth performance and feed efficiency are likely to result in lower production costs.…”
Section: Cost–benefit Analysis Of Using Probiotics In the Swine Industrymentioning
confidence: 99%
“…A variety of commercial probiotics for swine are currently available in the market, and small doses of these additives are frequently used. One study revealed that probiotics typically accounted for USD 13.65 billion in 2019 and are estimated to increase by 6.1% in 2027, depending on the manufacturer and the product’s active components [ 151 ]. In commercial pig farming, higher growth performance and feed efficiency are likely to result in lower production costs.…”
Section: Cost–benefit Analysis Of Using Probiotics In the Swine Industrymentioning
confidence: 99%
“…In the process of composting plant residues for compost production, many cellulolytic bacteria are also used [2]. Cellulolytic bacteria have been shown to be potential probiotics for ruminants [3]. Sheep with probiotic supplementary feed showed better biomass growth in all ages than sheep that were not supplemented with probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors can be adjusted to enhance enzyme productivity and yield, including media components such as carbon, nitrogen, mineral sources, additives, and inducers, as well as physical parameters like pH, aeration, and temperature. These factors play a crucial role in determining the cost of enzyme production, which is often considered a primary challenge in biotechnological processes [ 21 ]. Researchers typically use a one-variable-at-a-time (OVAT) approach to screen physical and chemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to identify optimal conditions and understand the specific impact of each variable. However, this method is time-consuming and may overlook interactions between variables, leading to suboptimal results [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%